Strategic Implementation of the IMT-GT Subregional Cooperation Blueprint 2022-2026 in Jambi Province - Rakhman, Moh Arief; Baidawi, Ahmad; Muhammad, Hatta Abdi; Dahlan, Fauzi (JOELS: Journal of Election and Leadership, 2025)
The Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) is a subregional cooperation initiative established in 1993 by the governments of Indonesia, Malaysia, and Thailand, aiming to accelerate economic transformation in less-developed provinces. IMT-GT meetings serve as a key building block for cooperation within ASEAN. Jambi Province, one of the 10 Indonesian provinces included in the IMT-GT program, is expected to benefit from the implementation of this initiative. The IMT-GT Blueprint for 2022-2026, which serves as the framework for subregional cooperation over the next five years, was finalized in 2022. Indonesia has outlined five main strategies for this blueprint: (1) economic corridor approach and regional integration, (2) promoting private sector participation, (3) supporting inclusive growth, (4) adopting green, blue, and circular economic  developments, and (5) institutional adjustments across sectors. Jambi Province has developed a designated area known as Sentusa (Sengeti, Tungkal, Sabak) to support the implementation of these strategies. This study focuses on the strategies employed by the provincial government of   Jambi to implement the IMT-GT framework. This research uses an exploratory descriptive method, gathering data from primary informants and secondary literature sources.